Control of manganese dioxide crystallographic structure in the redox reaction between graphene and permanganate ions and their electrochemical performance. Issue 28 (25th February 2015) - Ji, Chenchen; Ren, Haoqi; Yang, Shengchun
Abstract : MnO2 crystallographic structure was well controlled in the redox reaction between graphene and permanganate ions. Abstract : MnO2 with α + γ-, δ-, and α-phases were synthesized by using graphene as sacrificial template in a proposed KMnO4 –graphene–H2 SO4 reaction system. The as-prepared products were characterized with X-ray diffraction technique, Raman spectroscopy, and transmission electron microscopy. The structural analysis reveals that the cation concentration, i.e. H + and K +, has a profound effect on both the crystallographic structures and morphologies of the final products. The relatively higher K + concentration but lower H + concentration facilitates the formation of δ-phased MnO2 with a petal-like structure, and the lower concentration of both K + and H + cations is more conducive to the formation of a mixed phase of (α + γ) MnO2 . A further increase in the concentration of H +, forming the α-phased MnO2 nanorods is preferred. The electrochemical properties for supercapacitors indicate that the electrochemical performances of MnO2 strongly depend on their crystallographic structures, and they present a Faradaic reactivity sequence of δ- > α- > α + γ-MnO2 .